Mirror Images: The Novosti Press Agency Photograph Collection - Anderson, Jennifer (Archivaria, 2008)
The Novosti Press Agency Photograph Collection, held at Carleton University in its Special Collections and Archives, is a rare and fascinating resource. The seventy thousand photographs and accompanying text, dating from 1917 to 1991, originally belonged to the Soviet Novosti Press Agency (APN) bureau located on Charlotte Street in Ottawa, but were hurriedly gathered up by Carleton library staf f in late 1991 as the Soviet Union collapsed, and the press bureau closed up shop. Part of a campaign to persuade Westerners, and particularly Canadians, to view the USSR in a more positive light, the Ottawa APN distributed these photos and press releases to media outlets, or ganizations, and individuals across Canada. The collection of fers historians a glimpse of the constructed nature of the Soviet self-image, of ficial Soviet views on international relations during the Cold War, and attempts to soften antiSoviet opinions in Canada. In “Mirror Images,” Jennifer Anderson argues that the collection deserves to be better known amongst historians of Cold War Canada and international relations, and that the general public would also be intrigued by an exhibition, built around ideology, perception, and image-construction in the Cold War. RÉSUMÉ La collection de photographies de la Novosti Press Agency, conservée aux Special Collections and Archives de l’Université Carleton, est une ressource rare et fascinante. Les 70 000 photographies et les textes d’accompagnement, qui datent de 1917 à 1991, appartenaient autrefois au Bureau de la Soviet Novosti Press Agency (APN), situé sur la rue Charlotte à Ottawa, mais le personnel de la bibliothèque Carleton a dû récupérer ce matériel rapidement vers la fin de l’année 1991 avec la dissolution de l’Union soviétique et la fermeture du Bureau à Ottawa. Fondé en partie pour encourager les Occidentaux, en particulier les Canadiens, à voir l’URSS d’un meilleur œil, l’APN d’Ottawa distribuait ces photographies et ces communiqués de presse aux médias, aux or ganisations et aux individus à travers le Canada. La collection offre aux historiens un aperçu de la construction de l’image que se donnait l’Union soviétique, les points de vues soviétiques of ficiels sur les relations internationales pendant la Guerre froide et les ef forts pour adoucir les opinions anti-sovié- tiques au Canada. Dans son texte « Mirror Images », Jennifer Anderson soutient que la collection mérite d’être mieux connue des historiens de la Guerre froide au Canada et des historiens qui s’intéressent aux relations internationales et que le grand public pourrait aussi être intéressé par une exposition conçue autour de l’idéologie, de la perception et de la construction de l’identité pendant la Guerre froide.